Developing Based LKPD Problem Based Learning (PBL) To Increase Interest and Learning Results in Indonesian in the Elements of Poetry Class XI at SMA Negeri 8 Lubuk Linggau - Rosmalina, Een; Satinem, Satinem; Sari, Inda Puspita (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to develop teaching materials in the form of Student Worksheets (LKPD) based on Problem-Based Learning (PBL). To support its development, an initial review was conducted in several ways, namely literature review, observation and field research. This study uses a quantitative descriptive method. Data collection instruments include teacher needs analysis interviews, which include curriculum and learning resources, and student needs analysis questionnaires. The results of this study will be used to design learning media in the form of PBL-based Indonesian Language LKPD. Analysis of needs is carried out to identify teaching materials used by teachers, obstacles that arise during the learning process, and materials needed by students. After the researcher conducted a needs analysis, of the 32 students in grade XI of SMA Negeri 8 Lubuk Linggau, 87.50% had a study guidebook. The reality in the field, as many as 90.63% of students stated that the material on the elements of poetry contained in the guidebook was often concise and did not cover more complex aspects. As many as 74.07% of the available textbooks are still incomplete to be used as learning resources. As many as 87.50% of students need learning media in the hope of supporting learning activities and 93.75% of students need other learning media that can increase interest and learning outcomes. This shows that the development of teaching materials in the form of PBL-based LKPD is very much needed to support a more effective learning process and improve students' understanding of the elements of poetry.